Enhancement of piezoelectric energy harvesting with multi-stable nonlinear vibrations - Yang, Yaowen (2013)
The need for long-term solutions to power various wireless sensor systems has been driving the research in the area of energy harvesting for the past decade. The present paper brings forth an investigation into the realm of piezoelectric energy harvesting (PEH) using nonlinear vibrations. A piezoelectric cantilever beam with a magnetic tip mass interacting with additional magnets around it forms a multi-stable nonlinear PEH configuration. The study indicates that the multistable configuration provides a widened bandwidth as compared to the conventional linear PEH devices and an increased voltage output as compared to many other PEH devices. An experimental parametric study is conducted to arrive at an optimal configuration for the performance enhancement of the harvester along with a glimpse into the enhanced magnetostatic interactions equations and various possible magnetic nonlinear configurations for the given conditions.